1989
DOI: 10.1111/j.1471-4159.1989.tb07252.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Brain Interstitial Concentrations by Microdialysis

Abstract: Microdialysis is an extensively used technique for the study of solutes in brain interstitial space. The method is based on collection of substances by diffusion across a dialysis membrane positioned in the brain. The outflow concentration reflects the interstitial concentration of the substance of interest, but the relationship between these two entities is at present unclear. So far, most evaluations have been based solely on calibrations in saline. This procedure is misleading, because the ease by which mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
1
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(180 citation statements)
references
References 24 publications
8
169
1
2
Order By: Relevance
“…Thereafter, a further but unknown dilution of the drug occurs when it is distributed in the interstitial space. Methodological data (Beneviste et al, 1989) and theoretical predictions (Bungay et al, 1990) suggest that the concentration of a drug leaving the probe rapidly decreases in the area 1 mm from the probe.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, a further but unknown dilution of the drug occurs when it is distributed in the interstitial space. Methodological data (Beneviste et al, 1989) and theoretical predictions (Bungay et al, 1990) suggest that the concentration of a drug leaving the probe rapidly decreases in the area 1 mm from the probe.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds were quantified by electrochemical detection using a glassy carbon working electrode set at þ 400 mV against a silver-silver chloride reference electrode (WE-3G; Eicom, Kyoto, Japan), giving a detection limit for dopamine of about 0.02 pg/sample at a 2:1 signal-to-noise ratio. The probes had an in vitro recovery of approximately 12% for dopamine, but the reported concentrations were not adjusted for recovery in vivo because these estimations are inaccurate (Benveniste et al, 1989;Lindefors et al, 1989). Previous experiments in which we have used the same technique and procedure have shown that the dopamine efflux is more or less stabilized 16 h after probe insertion, EM-2-and EM-1-induced accumbal dopamine efflux H Okutsu et al and that the release seen at that time is largely dependent on neuronal release as more than 70% of the release is TTX sensitive (Saigusa et al, 2001).…”
Section: Dialysis and Neurochemical Measurementsmentioning
confidence: 99%
“…Drug treatment was administered by dissolving the corresponding compound at the specified concentration in the perf usion fluid. Although diff usion characteristics of probes may be different in brain matter than when tested in vitro (Benveniste et al, 1989), recovery for Ach and Cho in a static solution maintained at 37°C with a 5 mm membrane was assessed to provide an estimate of extracellular concentrations under the conditions used in our experiments. The average percentage in vitro recovery (ϮSEM) obtained with our probes against 0.6 M Ach and 8 M Cho when perf used at 0.7 l /min was Ach ϭ 41 Ϯ 5%, Cho ϭ 43 Ϯ 8%.…”
Section: Methodsmentioning
confidence: 99%